Pelatihan dan Pengenalan Konsep Agrowisata Guna Mendukung Pemanfaatan Tanah Bengkok Desa Kalisapu sebagai Daerah Agrowisata - Emik Rahayu; Izza Ulumuddin Ahmad Asshofi; Budi Santoso; Andi Hallang Lewa; Wijaya, Muhammad Askha Rafliansyach; Ariel Sabella Siva Shan (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Crooked land is customary land managed by the village whose designation is used for the benefit of the village or the administration of the village. By and large, crooked soil is used for agriculture. The use of crooked land as a source of village cash is not only in agriculture, but can also be through the field of tourism which is often referred to as agrotourism. The development of agrotourism by utilizing land based on local culture is expected to increase farmers' income and to reserve land resources, as well as maintain local culture and local technology (indigenous people's knowledge) which is generally in accordance with the natural conditions of the environment. In Kalisapu Village, most of the utilization of crooked land in Kalisapu village is still focused on agriculture as the main source of crooked land income. The crooked soil potential of the tourism field has not been optimally applied. To be able to develop crooked land into Agrotourism tourism, qualified and competent human resources are needed in Agrotourism tourism midwives. The training held is a collaboration between the Kalisapu Village Government, Slawi District, Central Java, and the proposing team of Dian Nuswantoro University (UDINUS) through a community service or community partnership program whose implementation is in the form of training, training and introduction to the concept of Agrotourism to support the use of crooked land in Kalisapu Village as an Agrotourism Area.